The Dynamic effects of Foreign Direct Investment Services and Energy Consumption on Information and Communication Technology Sector - Rawoof, Hira Abdul; Said, Laila Refiana; Irmak, Esma; Pelit, Irem; Shabbir, Malik Shahzad (International Journal of Energy Economics and Policy, 2023)
This study scrutinises the influence of foreign direct investment (FDI) inflows, energy consumption on Information and Communication services (ICTs) in selected economies of South Asia. This research is based on heterogenous and second generation framework of panel data-set from 1999 to 2021. This study used augmented mean group (AMG), mean group (MG), and common correlated effects mean group (CCEMG) assessors, which further promotes the substantial and favourable influence of FDI services, and energy consumption on ICTs. However, the impact of terrorism is insignificant on ICTs in the region of South Asia. The results indicate that economies of these region must embrace investment reform measures in order to draw FDI into the services sector, increase exports of services, and progress towards economic stability.